Micropropagation of Melissa officinalis L. - Topdemir, Aykut; Demir, Zümre; Gür, Nazmi (My University, 2016)
Lemon balm (Melissa officinalis L., Lamiaceae) is a well-known medicinal plant. Nodal and petiole explants of Melissa officinalis, cultured on MS medium supplemented with different combination and concentration of 2.4D, BAP, IAA, NAA, Picloram. The maximum shoot proliferation and elongation was obtained with BAP at 0.5 mg/lt and Picloram at 2mg/lt. 2.4 D and BAP combination had the best response to callus induction from petiole. Micropropagated plants were successfully transferred to soil.
Bildiri - Yayımlanmamış
Keywords: Melissa officinalis L; Lemon balm; Micropropagation; Regeneration